2002
DOI: 10.1046/j.1365-2265.2002.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between insulin secretion, the insulin‐like growth factor axis and growth in children with cystic fibrosis

Abstract: Impaired glucose tolerance was present in 20% of children with cystic fibrosis. Impaired insulin secretion was common (65%) even in children with normal glucose tolerance. The mean height SDS for the group was low and the height velocity was abnormally slow in 39%, yet nutritional status as measured by BMI was appropriate for age. Relative insulin deficiency rather than nutritional deprivation or poor clinical status thus appears to be implicated in the poor linear growth of these children with relatively stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 54 publications
3
43
2
3
Order By: Relevance
“…Taylor et al (28) described a progressive reduction of IGF-I and IGFBP-3 related to declining BMI, and deteriorating pulmonary function, and suggested that progressive insulin deficiency might be contributing to this. Ripa et al (29) further supported this hypothesis by showing a high frequency of insulin hyposecretion with increased serum IGFBP-1 levels, normal IGF-I and reduced growth velocity in CF. However, this group of patients had basal insulin levels similar or greater than controls.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Taylor et al (28) described a progressive reduction of IGF-I and IGFBP-3 related to declining BMI, and deteriorating pulmonary function, and suggested that progressive insulin deficiency might be contributing to this. Ripa et al (29) further supported this hypothesis by showing a high frequency of insulin hyposecretion with increased serum IGFBP-1 levels, normal IGF-I and reduced growth velocity in CF. However, this group of patients had basal insulin levels similar or greater than controls.…”
Section: Discussionsupporting
confidence: 55%
“…IGFBP-3 serum concentrations were similar in the patients and controls although they tended to be lower in patients with the most severe clinical state, and we did not find any relationship with insulin at variance with previously published data (28,29). This helps to explain why the IGF-I/IGFBP-3 molar ratios were similar in CF and healthy subjects.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The cross-sectional nature of our analysis could have introduced selection bias, although comparison of our population profile with that of previously published studies (6,19,26,27) suggests otherwise. The higher proportion of female than male subjects with CFRD was consistent with previously published data by Yung and Hodson (27), and the higher proportion of female than male subjects with CFRD and chronic P. aeruginosa was also consistent with those of Demko et al (6).…”
Section: Study Limitationsmentioning
confidence: 79%
“…This may result from a combination of poor nutrition, pancreatic insufficiency, chronic inflammatory lung disease, and intestinal disease. Even with vigorous treatment of these problems, including dietary interventions to provide calories and fat soluble vitamins in excess of usual recommended amounts [35], severe CF is associated with poor weight gain and slower growth [36]. Relative insulin deficiency rather than nutritional deprivation or poor clinical status may be implicated in the poor linear growth of children with relatively stable lung disease [36].…”
Section: Impaired Growth and Development And Impact Of Chronic Steroimentioning
confidence: 99%